(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This article aims to problematize the discourses of the written press in Chapecó (SC) regarding children and childhood in the 1970s. The newspaper Correio do Sul, published during that period, was chosen for this purpose. The journalistic discourse was analyzed based on the theoretical and methodological contributions of Michel Foucault. The text narrates the story of a boy arrested at the age of six and the machinations of the press to ascertain the facts and their veracity. In the context of the civil-military dictatorship, the newspaper’s discourse emerged as a challenging one, seeking to denounce social problems of the period. Furthermore, it highlights the ways in which the State protected those considered offenders and how it attempted to frame them as threats to social harmony.